Digital wine : how QR codes facilitate new markets for small wine industries - Brabazon, Tara; Winter, Mick; Gandy, Bryn (SpringerBriefs in Business,, 2014)
This book explores the way in which QR codes (Quick Response codes) can help the wine industry facilitate distribution and more effectively market and sell their product. It examines the interventions, invention and opportunities brought about by QR codes for the wine industry. It also investigates how QR codes can help enable regional development as well as information and knowledge about winemakers and regions.  The book begins with an introduction to QR codes. It explains how to use them as well as shows how QR codes combine analogue and online promotion and information dissemination. Next, the book explores strategies and examples from the creative industries, small nation theory and emerging wine industries. It then goes on to examine how to integrate QR codes with wine media, including marketing the bottle and using QR codes to build new wine regions. The book concludes with a case study of how Aotearoa/New Zealand wine producers deploy QR codes. QR codes can store, and digitally present, a range of helpful data, including URL links, geo-coordinates and text, and can be scanned by smart phones, making them a useful marketing and business tool. Presenting detail research on how QR codes can enhance the relationship between producers and consumers as well as aid regional development in the wine industry, this book  will be of interest to academics focusing on Wine Studies, small and medium sized enterprises (SMEs), and practitioners and researchers from the creative industries sector. In addition, while this book focuses on the wine industry, the information that it presents about QR codes is relevant and applicable for an array of industries that require a tether between analogue and digital, physical and virtual, especially food and primary production.